2021
DOI: 10.1088/2515-7655/abfb4a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in acoustic diagnostics for electrochemical power systems

Abstract: Over the last decade, acoustic methods, including acoustic emission (AE) and ultrasonic testing (UT), have been increasingly deployed for process diagnostics and health monitoring of electrochemical power devices, including batteries, fuel cells, and water electrolysers. These techniques are non-invasive, highly sensitive, and low-cost, providing a high level of spatial and temporal resolution and practicality. Their application in electrochemical devices is based on identifying changes in acoustic signals emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 155 publications
1
39
0
Order By: Relevance
“…The characteristics of the acoustic response of region D become blurred due to the rearrangement of the structure and lose its original characteristics, which is reflected in the chaos of the microstructure and change. These indicate a dramatic change in the mechanical properties of the electrode, which is consistent with the static mechanical analysis of the electrode [24,26,30]. From the perspective of the acoustic characteristics of a single short-circuit battery, in terms of the near-end frequency domain characteristics before, during, and after the ESC (window A-C), it is preliminarily shown that the value of the center frequency and its amplitude, which are representative, would characterize the change of the internal structure and the change of the mechanical properties when the short circuit occurs to a certain extent.…”
Section: Preliminary Analysis Of Acoustic Signalssupporting
confidence: 83%
See 1 more Smart Citation
“…The characteristics of the acoustic response of region D become blurred due to the rearrangement of the structure and lose its original characteristics, which is reflected in the chaos of the microstructure and change. These indicate a dramatic change in the mechanical properties of the electrode, which is consistent with the static mechanical analysis of the electrode [24,26,30]. From the perspective of the acoustic characteristics of a single short-circuit battery, in terms of the near-end frequency domain characteristics before, during, and after the ESC (window A-C), it is preliminarily shown that the value of the center frequency and its amplitude, which are representative, would characterize the change of the internal structure and the change of the mechanical properties when the short circuit occurs to a certain extent.…”
Section: Preliminary Analysis Of Acoustic Signalssupporting
confidence: 83%
“…At the same time, many macroscopic-level static strains of batteries have been associated with the operating state in the battery, which shows a strong correlation with the volume change in some pouch batteries. Acoustic measurements have also been used to detect possible macroscopic crack detection, and microscopic measurements have been used to further clarify the cause of the shock response in the electrochemical reaction of the battery [24,25]. However, critical explanations for battery fault diagnosis and acoustic detection feature extraction are still lacking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This continuation indicates that there is efficient internal mass transfer through the compact pore structure due to capillary forces . Large pores tend to empty preferentially according to the Young–Laplace equation, while small pores remain filled with the solvent for longer. ,, The onset of pore emptying has been identified as the first characteristic drying time associated with the start of an intermediate drying stage that is sensitive to high drying rates . This sensitivity can result in a detrimental loss of adhesion strength due to a depletion of the binder in the vicinity of the coating/substrate interface under high drying rates.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Upon cycling, batteries undergo variations in volume as great as 10%, resulting in mechanical stress (i.e., cracking) in the battery's materials. Hence, listening to the elastic acoustic waves generated during volume changes of battery materials before to analyze these waves [227] was used early for the Pb-acid and Ni-MH technologies [228] before being adapted for LIBs. [229,230] Indeed, AE is very effective for monitoring the different steps associated with battery operation, which includes the formatting step, as well as for detecting abusive operation conditions resulting in excessive stress in materials and potential safety issues.…”
Section: Acoustic Sensorsmentioning
confidence: 99%